Estimation on Mortality of Tropical Limpet Cellana testudinaria (Class : Gastropoda, Family : Patellidae) Living on the Rocky Shore of Ohoiwait, Southeast Moluccas, Indonesia - Abraham Seumel Khouw (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2004)
Sebanyak 2402 ekor limpet diperoleh dari 12 bulan pengambilan sampel yakni dari Oktober  2001 sampai September  2002. Rata-rata mortalitas limpet C. testudlnaria diestimasi dengan mempergunakan tiga metoda yang berbeda  dengan hasil adalah sebesar 94% per tahun (Z =2.81).  Mortalitas terbesar yang dilakukan dengan menggunakan pendekatan metoda Ault-Ehrhardt   dijumpai pada bulan Oktober 2001 dan April 2002, dimana terjadi kekeringan dan hempasan gelombang yang terbesar. Akan tetapi  tidak ada korelasi yang jetas antara mortalitas dan faktor-faktor  lingkungan. A total oF 2202 limpets were obtained  in 12 monthly collections (from October 2001 to September  2002). The mean mortality oF C. testudinaria was estimated, using three different methods;   reduction in the survival  of individual size frequency cohorts through  time, monthly calculation of the Ault  and Ehrhardt moment estimation, and length-converted catch curves. to be 94% per year  (Z = 2.81). Highest monthly mortality rates, determined with the Ault-Ehrhardt approach, were observed  in October 2001 and April  2002,  when  desiccation  stress (temperature of the rocky  surface  was about  4O0C) and  wave  action  (was about  3 m),  respectively,    were highest   However,   there  was no significant linear correlation  between  mortality and environmental   variables.